2014
DOI: 10.1002/hep.27053
|View full text |Cite
|
Sign up to set email alerts
|

All-oral combination of ledipasvir, vedroprevir, tegobuvir, and ribavirin in treatment-naïve patients with genotype 1 HCV infection

Abstract: This phase II trial assessed the efficacy and safety of a combination regimen of the nonstructural protein (NS)5A inhibitor ledipasvir (LDV), NS3 protease inhibitor vedroprevir (VDV), non-nucleoside NS5B inhibitor tegobuvir (TGV), and ribavirin (RBV) in treatment-na€ ıve patients with chronic hepatitis C virus (HCV) genotype 1 without cirrhosis. Patients were randomized 1:2 to LDV 30 mg once daily (QD; Arm 1; n 5 46) or LDV 90 mg QD (Arm 2; n 5 94); patients in both arms also received VDV 200 mg QD, TGV 30 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 12 publications
(24 reference statements)
0
28
0
Order By: Relevance
“…However, both in vitro studies and clinical trials with different classes of direct-acting antiviral (DAA) agents (NS3 protease, NS5A-, and nucleos[t]ide and nonnucleos[t]ide NS5B-polymerase inhibitors), given with PR or in interferon-free combinations, have shown lower response rates for HCV genotype 1a than for HCV genotype 1b (2)(3)(4)(5)(6)(7)(8). Moreover, at least for HCV genotype 1, both the frequency and the pattern of resistance to different DAA classes are subtype specific (9). A striking example is the NS3-Q80K polymorphism, naturally found in Ͼ30% of naive subtype 1a patients but in Ͻ1% of subtype 1b patients (10), which conveys 30%-to-40%-lower sustained-virologic-response (SVR) rates to the macrocyclic protease inhibitor simeprevir (2).…”
mentioning
confidence: 99%
“…However, both in vitro studies and clinical trials with different classes of direct-acting antiviral (DAA) agents (NS3 protease, NS5A-, and nucleos[t]ide and nonnucleos[t]ide NS5B-polymerase inhibitors), given with PR or in interferon-free combinations, have shown lower response rates for HCV genotype 1a than for HCV genotype 1b (2)(3)(4)(5)(6)(7)(8). Moreover, at least for HCV genotype 1, both the frequency and the pattern of resistance to different DAA classes are subtype specific (9). A striking example is the NS3-Q80K polymorphism, naturally found in Ͼ30% of naive subtype 1a patients but in Ͻ1% of subtype 1b patients (10), which conveys 30%-to-40%-lower sustained-virologic-response (SVR) rates to the macrocyclic protease inhibitor simeprevir (2).…”
mentioning
confidence: 99%
“…This finding may explain the low rates of virologic breakthrough seen in the phase 3 clinical trials of ABT-450/r, ombitasvir, and dasabuvir with or without RBV, since similarly constructed drug regimens that did not use pharmacokinetic enhancement have been associated with high rates of virologic breakthrough (51,52). In addition, the lower dosing of ABT-450, facilitated by the boosting effect of ritonavir, may correlate with the low rates of treatment discontinuation and good tolerability seen in these large clinical trials (19)(20)(21)(22)(23).…”
Section: Resultsmentioning
confidence: 99%
“…Ledipasvir several studies have shown its value as a combination therapy with other DAA therapies, other than SOF. [18] The current recommendation for LDV use suggests there is no need to combine LDV/SOF with RBV or to prolong the treatment duration for more than 12 weeks. [19] Moreover, a more recent study recommends that a patient with HCV RNA level of < 6 million IU/mL may need LDV/SOF for only an 8-weeks treatment schedule.…”
Section: Sofosbuvirmentioning
confidence: 99%